Comparison of intermittent and continuous palliative chemotherapy for advanced colorectal cancer: a multicentre randomised trial. - Maughan, T; James, R; Kerr, D; Ledermann, J; Seymour, M; Topham, C; McArdle, C; Cain, D; Stephens, R (2003)
BACKGROUND: Policies of UK clinicians regarding the duration of chemotherapy for patients with advanced colorectal cancer are not consistent. We aimed to compare effectiveness of continuous and intermittent chemotherapy in such patients. METHODS: Patients who responded or had stable disease after receiving 12 weeks of the regimens described by de Gramont and Lokich, or raltitrexed chemotherapy, were randomised to either intermittent (a break in chemotherapy, re-starting on the same drug on progression), or continuous chemotherapy until progression. FINDINGS: 354 patients (178 intermittent, 176 continuous) were enrolled from 42 UK centres. At randomisation, 41% of participants had part or complete response; 59% were stable. Only 66 (37%) patients allocated to intermittent treatment restarted as planned, after a median of 130 days. Median time on treatment after restarting was 84 days. Patients in the continuous group remained on treatment for a median of a further 92 days. Similar proportions of patients in both groups received second-line therapy. Patients on intermittent chemotherapy had significantly fewer toxic effects and serious adverse events than those in the continuous group. There was no clear evidence of a difference in overall survival (hazard ratio 0.87 favouring intermittent, 95% CI 0.69-1.09, p=0.23). INTERPRETATION: Our findings provided no clear evidence of a benefit in continuing therapy indefinitely until disease progression. They showed that it is safe to stop chemotherapy after 12 weeks and re-start the same treatment on progression in patients with chemosensitive advanced colorectal cancer.